1994
DOI: 10.1364/ao.33.001938
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of birefringence for optical recording of disk substrates

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…(2), the DC component I and the quadrature AC components of beat signal J,, and are given by 'DC a?, (3) Ix = ar al L cos 2p, (4) ly = ar a A sin 2p. (5) In Eq. (3), (4) and (5), since we can adjust to the equal amplitudes ofleft and right circular polarization components; ie a1 = a,, then A and p of the sample are calculated as follow,…”
Section: Principle and Experimental Setupmentioning
confidence: 99%
“…(2), the DC component I and the quadrature AC components of beat signal J,, and are given by 'DC a?, (3) Ix = ar al L cos 2p, (4) ly = ar a A sin 2p. (5) In Eq. (3), (4) and (5), since we can adjust to the equal amplitudes ofleft and right circular polarization components; ie a1 = a,, then A and p of the sample are calculated as follow,…”
Section: Principle and Experimental Setupmentioning
confidence: 99%
“…Several authors have reported on the measurements of birefringence (both lateral and vertical) using various ellipsometric techniques. [5][6][7][8] These measurements tend to be elaborate, time-consuming, and confined to probing one small area at a time. Most often, these measurements are also intrusive in that they either slice and destroy the substrate, or render it unsuitable for further processing by the application of index-matching fluid during the measurement.…”
Section: Advantagesmentioning
confidence: 99%
“…In (b) the At λ = 633 nm and with a measured pe riod of L = 1.05 mm, the above formula yields Δn⊥ -6 X 10 -4 , which is consistent with other measurements of the same substrate. 8 The period of oscillations can be derived fairly accurately from a Fourier spectrum of the intensity patterns of Figure 2. Figure 3 shows the spectrum of the signal displayed in Fig.…”
Section: System Descriptionmentioning
confidence: 99%
“…Mansuripur's group [8][9][10] has developed techniques to measure both in-plane and vertical birefringence of an optical disc. This technique extracts the birefringence measuring polarization variations and fitting these to models generated in Multilayer system analysis software, without giving the explicit relation between the polarization variation and birefringence.…”
Section: Introductionmentioning
confidence: 99%